Asymmetric benzoxazine-based interfacial compatibilizer as well as preparation method and application thereof

By using asymmetric benzoxazine monomers as interface compatibilizers, the plant fibers are directly coated, and the problems of complex modification process and reduced fiber performance in the prior art are solved, and the effect of improving the hydrophobicity and flame retardant properties of the fiber is achieved.

CN119823527APending Publication Date: 2025-04-15长三角碳纤维及复合材料技术创新中心
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411921666.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art usually requires complex processing conditions when modifying plant fibers, which easily lead to fiber structure failure and performance degradation.

Method used

Asymmetric benzoxazine monomer is used as the interface compatibilizer to directly physically coat plant fibers to improve the hydrophobicity and flame retardancy of the fibers, and the operation is simple and does not damage the fibers.

Benefits of technology

It improves the hydrophobicity and flame retardant properties of plant fibers, significantly improves the interface strength and performance of composite materials, and avoids damage to fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823527A_ABST
    Figure CN119823527A_ABST
Patent Text Reader

Abstract

The invention discloses an asymmetric benzoxazine-based interfacial compatibilizer and a preparation method and application thereof.Arbutin and beta-naphthol are used as phenol sources, diamine is used as an amine source, an asymmetric benzoxazine monomer is prepared through a step-by-step condensation method, the asymmetric benzoxazine monomer has amphipathy and serves as an interfacial modifier to directly coat plant fibers, the fibers are not damaged, and the asymmetric benzoxazine-based interfacial compatibilizer can be used for preparing the plant fibers. The hydrophobicity and the flame retardance of the fiber are improved. Wherein monosaccharide molecules in the arbutin can form abundant hydrogen bond interaction with the surface of the plant fiber, naphthyl can form stable pi-pi interaction with a commercially available benzoxazine matrix, and co-curing is carried out, so that the plant fiber reinforced composite material with excellent performance and strong interface bonding is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plant fiber composite materials, and specifically is an asymmetric benzoxazine-based interfacial compatibilizer and a preparation method and application thereof. Background Art

[0002] In recent years, green composite materials based on plant fiber reinforcement have attracted wide attention due to their advantages such as light weight, high strength, and green environmental protection. As a biomass with cellulose as the main component, plant fiber itself has high flammability and hygroscopicity. At the same time, there are a large number of polar alcohol hydroxyl groups on its surface, which have poor compatibility with most polymer matrices, resulting in poor interfacial properties of composite materials. Therefore, the modification of plant fiber is very necessary, and the commonly used modification methods mainly include chemical reactions (such as esterification, silane reaction) and physical treatments (such as plasma treatment, laser treatment, etc.). For example, patent CN107603209B discloses a method for preparing an acetylated modified plant fiber reinforced nylon 6 composite material, wherein the acetylated modification of natural fiber requires heating reaction at 50 to 100 ° C in catalysts such as sulfuric acid, perchloric acid, and N-bromosuccinimide for 2 to 12 hours. Patent CN110230205A discloses a method for modifying plant fibers, modified plant fibers, plant fiber-reinforced composite materials, and preparation methods thereof, wherein the modification of plant fibers requires the use of erucic acid, palmitic acid, or dodecyl bromide to initiate an esterification reaction. It is not difficult to see that these methods usually require complex processing conditions, which can easily lead to fiber structure damage and reduced performance. Summary of the invention

[0003] The technical problem to be solved by the present invention is: in view of the technical problems existing in the prior art, the present invention provides an asymmetric benzoxazine-based interfacial compatibilizer and a preparation method and application thereof, by preparing an asymmetric benzoxazine monomer to make it amphiphilic, and using it as an interfacial modifier to directly coat plant fibers, the operation is simple, the fibers are not damaged, and the hydrophobicity and flame retardancy of the fibers are improved.

[0004] In order to solve the above technical problems, the technical solution proposed by the present invention is:

[0005] An asymmetric benzoxazine-based interfacial compatibilizer comprises an asymmetric benzoxazine monomer and a low-polarity organic solvent, wherein the asymmetric benzoxazine monomer has a general structural formula of:

[0006]

[0007] Wherein, R is one of a C1-C20 alkyl group and a substitution product thereof, a phenyl group and a substitution product thereof.

[0008] As a further improvement of the above technical solution:

[0009] In the above technical solution, the low-polarity organic solvent includes one or a mixture of more than one of dichloromethane, chloroform, ethyl acetate, methyl ethyl ketone, ethyl ether, dioxane, and tetrahydrofuran.

[0010] The present invention synthesizes an asymmetric benzoxazine containing both a monosaccharide group and a naphthyl group, which is used for direct physical coating of plant fibers to activate the interface, thereby improving the fiber performance and composite material performance while avoiding complicated processing and damage to the fiber.

[0011] The present invention also provides a method for preparing an asymmetric benzoxazine-based interfacial compatibilizer. The preparation method first uses arbutin and β-naphthol as phenol sources and diamine as amine source to prepare an asymmetric benzoxazine monomer by a step-by-step condensation method; then the asymmetric benzoxazine monomer and an organic solvent are mixed, stirred and dissolved, and the concentration range of the asymmetric benzoxazine monomer is 1 to 10 wt.%.

[0012] In the above technical solution, the method for synthesizing the asymmetric benzoxazine monomer comprises the following steps:

[0013] Step S1, adding β-naphthol, diamine and paraformaldehyde to dioxane, and reflux reaction for 18 to 24 hours, the reaction equation is:

[0014]

[0015] Step S2, adding paraformaldehyde and arbutin, and reflux reaction for 10 to 12 hours, the reaction equation is:

[0016]

[0017] 3) After the reaction is completed, excess solvent is removed by rotary evaporation, and the product is purified by recrystallization and dried to obtain an asymmetric benzoxazine-based interfacial compatibilizer.

[0018] In the above technical solution, in step S1, the ratio of β-naphthol, diamine and paraformaldehyde is 1:1:2.

[0019] In the above technical solution, in step S2, 2 equivalents of paraformaldehyde are added, and 1 equivalent of arbutin is added.

[0020] The present invention also provides an application of the asymmetric benzoxazine-based interfacial compatibilizer in interfacial modification of benzoxazine resin or plant fiber reinforced composite materials.

[0021] In the above technical solution, the plant fibers include but are not limited to flax fibers, ramie fibers, jute fibers, sisal fibers, and cellulose fibers.

[0022] In the above technical solution, the benzoxazine resin includes one or more of bisphenol A type, bisphenol F type, diamine type, biphenyl type, allyl type, etc.

[0023] In the above technical solution, the preparation method of the interface-compatibilized benzoxazine resin or plant fiber-reinforced composite material includes plant fiber surface treatment, resin compounding and molding processing.

[0024] In the above technical scheme, the plant fiber surface treatment method comprises the following steps: directly immersing the plant fiber in an asymmetric benzoxazine-based interfacial compatibilizer, and obtaining modified plant fiber after heating and vacuum drying after immersion, wherein the immersion time ranges from 1 to 3 hours, the vacuum drying temperature ranges from 40 to 80°C, and the drying time ranges from 2 to 5 hours.

[0025] The asymmetric benzoxazine-based interfacial compatibilizer provided by the present invention and its preparation method and application have the following advantages compared with the prior art:

[0026] (1) The asymmetric benzoxazine-based interfacial compatibilizer of the present invention, and its preparation method and application, synthesize an asymmetric benzoxazine monomer to make it amphiphilic, wherein the hydrophilic monosaccharide group forms abundant hydrogen bond interactions with plant fibers through hydrogen bond interactions, and the hydrophobic naphthyl group and the benzoxazine monomer undergo π-π stacking interactions; the fiber is treated by direct immersion, which is simple to operate and does not require chemical reaction treatment or plasma treatment of the fiber, thereby minimizing damage to the fiber and improving the hydrophobicity and flame retardant properties of the fiber.

[0027] (2) The asymmetric benzoxazine-based interfacial compatibilizer of the present invention, its preparation method and application, directly use benzoxazine monomer as the effective component of the compatibilizer, so that the resin and the compatibilizer are homologous, and a copolymerization reaction can occur between the two, further enhancing the interfacial adhesion, thereby significantly improving the interfacial strength of the composite material. Compared with the composite material prepared from unmodified fibers, its interlaminar shear strength and impact strength are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 These are the scanning electron microscope images of unmodified ramie fiber and NA-pda modified ramie and the N element energy spectrum. DETAILED DESCRIPTION

[0029] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0030] The asymmetric benzoxazine monomer used in the examples of the present invention is homemade, and other raw materials are purchased from the market.

[0031] The instruments and equipment used in the examples are all conventional equipment in the relevant fields, and the performance tests are all in accordance with the requirements of conventional standards.

[0032] Embodiment 1:

[0033] Weigh 1 part of β-naphthol, 1 part of 1,3-propylenediamine, and 2 parts of paraformaldehyde, add them to 4 parts of dioxane, heat under reflux and react for 20 hours after fully dissolving, then add 1 part of arbutin and 2 parts of paraformaldehyde, continue to react for 10 hours, remove excess solvent by rotary evaporation, and use a mixed solvent of ethyl acetate / petroleum ether in a ratio of 3:1 for recrystallization and purification to obtain an asymmetric benzoxazine monomer (NA-pda);

[0034] The benzoxazine monomer is dissolved in an appropriate amount of chloroform to prepare a solution with a concentration of 5 wt.% as an interface compatibilizer;

[0035] Another appropriate amount of cellulose fibers was taken and immersed in the organic solution for 2 hours. Then, the fibers were taken out and vacuum dried at 65°C for 2.5 hours to obtain NA-pda modified cellulose fibers. Figure 1 As shown, after testing, the maximum heat release rate of MCC of the unmodified fiber is 385.7W / g, and the static contact angle of the fiber cloth is 34.2°. After modification, the total heat release of MCC of the fiber is 141.6W / g, and the static contact angle of the fiber cloth is 88.3°;

[0036] The modified cellulose fiber and bisphenol A benzoxazine were hand-laminated and then heated at 140°C for 2 hours and 220°C for 4 hours to obtain a benzoxazine-based plant fiber reinforced composite material. The composite material has a tensile strength of 103.7MPa, a flexural strength of 125.5MPa, and an impact strength of 7.22kJ / m 2 , the interlaminar shear strength is 12.01MPa.

[0037] Embodiment 2:

[0038] Weigh 1 part of β-naphthol, 1 part of diethylenetriamine, and 2 parts of paraformaldehyde, add them to 4 parts of dioxane, heat and reflux to react for 18 hours after fully dissolving, then add 1 part of arbutin and 2 parts of paraformaldehyde, continue to react for 10 hours, remove excess solvent by rotary evaporation, and use a mixed solvent of ethyl acetate / petroleum ether 2:1 for recrystallization and purification to obtain an asymmetric benzoxazine monomer (NA-deta);

[0039] The benzoxazine monomer is dissolved in an appropriate amount of ethyl acetate to prepare a solution with a concentration of 1 wt.% as an interfacial compatibilizer;

[0040] Another amount of ramie fiber was taken and soaked in an organic solution for 3 hours. Then, the fiber was taken out and placed in a vacuum dryer at 40°C for 5 hours to obtain NA-deta modified ramie fiber. After testing, the maximum heat release rate of MCC of the unmodified fiber was 402.3 W / g, and the static contact angle of the fiber cloth was 42.3°. After modification, the total heat release of MCC of the fiber was 211.5 W / g, and the static contact angle of the fiber cloth was 82.3°;

[0041] The modified ramie fiber and bisphenol F benzoxazine were compounded by pressure bag molding, and then heated at 120°C for 6 hours and 180°C for 6 hours to obtain a benzoxazine-based plant fiber reinforced composite material. The composite material was tested to have a tensile strength of 95.0MPa, a flexural strength of 118.6MPa, and an impact strength of 7.15kJ / m 2 , the interlaminar shear strength is 12.36MPa.

[0042] Embodiment 3:

[0043] Weigh 1 part of β-naphthol, 1 part of p-phenylenediamine, and 2 parts of paraformaldehyde, add them to 4 parts of dioxane, heat and reflux to react for 24 hours after fully dissolving, then add 1 part of arbutin and 2 parts of paraformaldehyde, continue to react for 12 hours, remove excess solvent by rotary evaporation, and use a mixed solvent of chloroform / n-hexane in a ratio of 2:1 for recrystallization and purification to obtain an asymmetric benzoxazine monomer (NA-phda);

[0044] The benzoxazine monomer is dissolved in an appropriate amount of dichloromethane to prepare a solution with a concentration of 10 wt.% as an interface compatibilizer;

[0045] Take an appropriate amount of flax fiber and soak it in an organic solution for 1 hour. Then, take out the fiber and place it under vacuum drying at 45°C for 4.5 hours to obtain NA-phda modified flax fiber. After testing, the maximum heat release rate of MCC of the unmodified fiber is 432.1W / g, and the static contact angle of the fiber cloth is 50.6°. After modification, the total heat release of MCC of the fiber is 189.6W / g, and the static contact angle of the fiber cloth is 96.0°;

[0046] The modified flax fiber and phenol-4'4-diaminodiphenylmethane benzoxazine were compounded by pultrusion, and then heated at 180°C for 2 hours and 260°C for 2 hours to obtain a benzoxazine-based plant fiber reinforced composite material. The composite material has a tensile strength of 91.4MPa, a flexural strength of 113.6MPa, and an impact strength of 7.56kJ / m 2 , the interlaminar shear strength is 11.79MPa.

[0047] Embodiment 4:

[0048] Weigh 1 part of β-naphthol, 1 part of isophorone diamine, and 2 parts of paraformaldehyde, add them to 4 parts of dioxane, heat and reflux to react for 20 hours after fully dissolving, then add 1 part of arbutin and 2 parts of paraformaldehyde, continue to react for 11 hours, remove excess solvent by rotary evaporation, and use a mixed solvent of ethyl acetate / petroleum ether in a ratio of 3:1 for recrystallization and purification to obtain an asymmetric benzoxazine monomer (NA-ipda);

[0049] The benzoxazine monomer is dissolved in an appropriate amount of methyl ethyl ketone to prepare a solution with a concentration of 8 wt.% as an interface compatibilizer;

[0050] Take another appropriate amount of jute fiber and soak it in an organic solution for 2.5 hours. Then, take out the fiber and place it under vacuum drying at 80°C for 2 hours to obtain NA-ipda modified jute fiber. After testing, the maximum heat release rate of MCC of the unmodified fiber is 396.7W / g, and the static contact angle of the fiber cloth is 39.0°. After modification, the total heat release of MCC of the fiber is 158.9W / g, and the static contact angle of the fiber cloth is 92.4°;

[0051] The modified jute fiber and allyl benzoxazine were molded and compounded, and then heated at 160°C for 4 hours and 240°C for 4 hours to obtain a benzoxazine-based plant fiber reinforced composite material. The composite material has a tensile strength of 90.7MPa, a flexural strength of 119.9MPa, and an impact strength of 7.88kJ / m 2 , the interlaminar shear strength is 10.89MPa.

[0052] Embodiment 5:

[0053] Weigh 1 part of β-naphthol, 1 part of 1,4-cyclohexanediamine, and 2 parts of paraformaldehyde, add them to 4 parts of dioxane, heat and reflux to react for 22 hours after fully dissolving, then add 1 part of arbutin and 2 parts of paraformaldehyde, continue to react for 12 hours, remove excess solvent by rotary evaporation, and use a mixed solvent of ethyl acetate / petroleum ether in a ratio of 3:1 for recrystallization and purification to obtain an asymmetric benzoxazine monomer (NA-chda);

[0054] The benzoxazine monomer is dissolved in an appropriate amount of a 1:1 mixed solvent of dioxane / dichloromethane to prepare a solution with a concentration of 5 wt.% as an interface compatibilizer;

[0055] Take an appropriate amount of sisal fiber and soak it in an organic solution for 2 hours. Then, take out the fiber and place it under vacuum drying at 70°C for 2 hours to obtain NA-chda modified sisal fiber. After testing, the maximum heat release rate of MCC of the unmodified fiber is 421.1W / g, and the static contact angle of the fiber cloth is 40.5°. After modification, the total heat release of MCC of the fiber is 177.4W / g, and the static contact angle of the fiber cloth is 85.2°;

[0056] The modified sisal fiber and biphenyl benzoxazine were composited by fiber winding, and then heated at 150°C for 5 hours and 230°C for 3 hours to obtain a benzoxazine-based plant fiber reinforced composite material. The composite material has a tensile strength of 84.6MPa, a flexural strength of 108.7MPa, and an impact strength of 8.12kJ / m 2 , the interlaminar shear strength is 10.56MPa.

[0057] Comparative Example 1:

[0058] The difference between this comparative example and Example 1 is that the fiber is not modified and other operations remain unchanged.

[0059] The composite material obtained in this comparative example has a tensile strength of 72.6 MPa, a flexural strength of 78.5 MPa, and an impact strength of 5.22 kJ / m 2 , the interlaminar shear strength is 7.33MPa.

[0060] Comparative Example 2:

[0061] The difference between this comparative example and Example 2 is that commercially available bisphenol A type benzoxazine monomer is used as an interfacial compatibilizer to modify the fiber, and other operations remain unchanged.

[0062] The total heat release of the modified fiber MCC obtained in this comparative example is 258.2W / g, and the static contact angle of the fiber cloth is 46.0°; the tensile strength of the composite material obtained is 75.4MPa, the flexural strength is 92.3MPa, and the impact strength is 4.84kJ / m 2 , the interlaminar shear strength is 8.36MPa.

[0063] Comparative Example 3:

[0064] The difference between this comparative example and Example 3 is that in the first step of synthesizing the benzoxazine monomer, β-naphthol is used instead of arbutin to synthesize the symmetrical benzoxazine monomer NN-pda as an interfacial compatibilizer component for modifying the fiber, and other operations remain unchanged.

[0065] The total heat release of the modified fiber MCC obtained in this comparative example is 231.3W / g, and the static contact angle of the fiber cloth is 53.4°; the tensile strength of the composite material obtained is 74.9MPa, the flexural strength is 91.0MPa, and the impact strength is 5.39kJ / m 2 , the interlaminar shear strength is 8.21MPa.

[0066] Comparative Example 4:

[0067] The difference between this comparative example and Example 4 is that in the second step of synthesizing the benzoxazine monomer, arbutin is used instead of β-naphthol to synthesize the symmetrical benzoxazine monomer AA-pda as an interfacial compatibilizer component for modifying the fiber, and other operations remain unchanged.

[0068] The total heat release of the modified fiber MCC obtained in this comparative example is 212.3W / g, and the static contact angle of the fiber cloth is 45.3°; the tensile strength of the composite material obtained is 21.1MPa, the flexural strength is 98.4MPa, and the impact strength is 5.51kJ / m 2 , the interlaminar shear strength is 9.44MPa.

[0069] Table 1 Properties of plant fibers and benzoxazine-based composite materials obtained in Examples 1-5 and Comparative Examples 1-3

[0070]

[0071]

[0072] The comparison results are shown in Table 1. In addition, the inventors of this case also conducted experiments with other raw materials, process operations, and process conditions described in this specification with reference to the aforementioned embodiments, and obtained relatively ideal results.

[0073] The above implementation cases are only preferred embodiments of the present invention and are not intended to limit the present invention in any form. Although the present invention has been disclosed as above with preferred embodiments, they are not intended to limit the present invention. Therefore, any simple modification, equivalent changes and modifications made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection of the technical solution of the present invention.

Claims

1. An asymmetric benzoxazine-based interfacial compatibilizer, characterized in that: The invention comprises an asymmetric benzoxazine monomer and a low-polarity organic solvent, wherein the asymmetric benzoxazine monomer has the general structural formula: Wherein, R is one of a C1-C20 alkyl group and a substitution product thereof, a phenyl group and a substitution product thereof.

2. The asymmetric benzoxazine-based interfacial compatibilizer according to claim 1, characterized in that: The low-polarity organic solvent includes one or a mixture of more than one of dichloromethane, chloroform, ethyl acetate, methyl ethyl ketone, ethyl ether, dioxane, and tetrahydrofuran.

3. A method for preparing an asymmetric benzoxazine-based interfacial compatibilizer, characterized in that: The asymmetric benzoxazine-based interfacial compatibilizer according to claim 1 is prepared by using arbutin and β-naphthol as phenol sources and diamine as amine source to prepare an asymmetric benzoxazine monomer by a step-by-step condensation method; then the asymmetric benzoxazine monomer and an organic solvent are mixed, stirred and dissolved, and the concentration of the asymmetric benzoxazine monomer is in the range of 1 to 10 wt.%.

4. The method for preparing the asymmetric benzoxazine-based interfacial compatibilizer according to claim 3, characterized in that: The synthesis method of the asymmetric benzoxazine monomer comprises the following steps: Step S1, adding β-naphthol, diamine and paraformaldehyde to dioxane, and reflux reaction for 18 to 24 hours, the reaction equation is: Step S2, adding paraformaldehyde and arbutin, and reflux reaction for 10 to 12 hours, the reaction equation is: 3) After the reaction is completed, excess solvent is removed by rotary evaporation, and the product is purified by recrystallization and dried to obtain an asymmetric benzoxazine-based interfacial compatibilizer.

5. The method for preparing the asymmetric benzoxazine-based interfacial compatibilizer according to claim 4, characterized in that: In the step S1, the ratio of β-naphthol, diamine and paraformaldehyde is 1:1:

2.

6. The method for preparing the asymmetric benzoxazine-based interfacial compatibilizer according to claim 4, characterized in that: In the step S2, 2 equivalents of paraformaldehyde and 1 equivalent of arbutin are added.

7. Use of the asymmetric benzoxazine-based interfacial compatibilizer according to claim 1 in interfacial modification of benzoxazine resin or plant fiber reinforced composite materials.

Citation Information

Patent Citations

  • A method for preparing acetylated plant fiber reinforced nylon 6 composite material

    CN107603209B

  • Modified method of plant fiber and modified plant fiber, plant fiber reinforced composite material and preparation method of plant fiber reinforced composite material

    CN110230205A